2021
DOI: 10.3389/fneur.2021.636573
|View full text |Cite
|
Sign up to set email alerts
|

Contralesional Structural Plasticity in Different Molecular Pathologic Subtypes of Insular Glioma

Abstract: Neuroplasticity may preserve neurologic function in insular glioma, thereby improving prognosis following resection. However, the anatomic and molecular bases of this phenomenon are not known. To address this gap in knowledge, the present study investigated contralesional compensation in different molecular pathologic subtypes of insular glioma by high-resolution three-dimensional T1-weighted structural magnetic resonance imaging. A total of 52 patients with insular glioma were examined. We compared the gray m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…The fact that slow-growing lesions lead to elevated cortical volume in the contralesional hemisphere has been reproduced multiple times [ 15 , 19 , 27 , 28 ], and has also been demonstrated in the current research ( Figure 1 ). Unlike previous studies, we also observed global and local characteristics in the contralateral structural connectivity network at the white matter level and found that GM volume and WM connectivity were consistent.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The fact that slow-growing lesions lead to elevated cortical volume in the contralesional hemisphere has been reproduced multiple times [ 15 , 19 , 27 , 28 ], and has also been demonstrated in the current research ( Figure 1 ). Unlike previous studies, we also observed global and local characteristics in the contralateral structural connectivity network at the white matter level and found that GM volume and WM connectivity were consistent.…”
Section: Discussionsupporting
confidence: 82%
“…Activation of the compensation ability often alleviates original tumor-induced dysfunction [ 6 , 13 ]. Lesions or trauma can activate the brain’s structural and functional potential in its undamaged parts [ 14 ], manifested by increased cortical volume [ 15 ] and enhanced functional connectivity [ 16 ]. Previous studies have suggested that functional compensation mostly occurs in the area around the lesion [ 6 , 13 , 16 ], while more recent findings indicate that for lesions anchored in eloquent areas, the homotopic area on the opposite side of the lesion is more likely to be the area where functional compensation occurs [ 12 , 15 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cortical plasticity pattern of gliomas is hierarchical (60). This hierarchical pattern is particularly suitable for LGGs because they show the characteristics of slow growth and low invasiveness, which leaves enough time for the process of plasticity (61). It should be noted that based on the 2016 version, the 2021 version of the WHO CNS tumor classification system (Fifth Edition) further promotes the importance of molecular diagnosis in the comprehensive diagnosis of CNS tumors, which is highly correlated with tumor aggressiveness and prognosis (11,62,63).…”
Section: Dti/20 Patients and 20 Hcs/graph Theorymentioning
confidence: 99%
“…Such homotopic reorganization has been reported in previous studies, eg, it has been reported that insular glioma leads to greater GMV in the contralesional insular, and that slow-growing frontal gliomas trigger overactivation in contralesional homotopic regions. 6,23 Indeed, as the key region involved in higher-order executive functions, the executive function of the brain can be affected by frontal glioma. 24 Interestingly, clinical observations indicate that patients with frontal gliomas retain intact executive function.…”
Section: Cortical Thickness Compensations In the Contralateral Hemisp...mentioning
confidence: 99%